Jacques Gilard y el alegato sobre la República Criolla - Fabio Rodríguez Amaya (Caravelle)
This work is an approach to Jacques Gilard’s treatment towards culture, identity and literature of the República Criolla in the crucial decades of 1940-1950, among a series of solid essays (some are considered seminal) that he dedicated to such problems in Colombia during his university career. The thought, the main characters, the social and political conditions of the country are reviewed and, after tracing an ideal sequence of the French critic’s thought, comes the elaboration of a large reflection about a subject that today, as well as by the past, assumes a great importance.